2008
DOI: 10.1051/0004-6361:200810440
|View full text |Cite
|
Sign up to set email alerts
|

The environmental dependence of properties of galaxies around the RDCSJ0910+54 cluster atz = 1.1

Abstract: We report on the environmental dependence of properties of galaxies around the RDCSJ0910+54 cluster at z = 1.1. We obtained multi-band wide-field images of the cluster with Suprime-Cam and MOIRCS on Subaru and WFCAM on UKIRT. Also, an intensive spectroscopic campaign was carried out using LRIS on Keck and FOCAS on Subaru. We collected 161 spectra with secure redshifts, with which we calibrated a larger sample of photometric redshifts. We discover a possible large-scale structure around the cluster in the form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 55 publications
(89 reference statements)
4
48
1
Order By: Relevance
“…15. At the same time, the fiducial members of XMMU J0338.7+0030 that are classified as elliptical galaxies populate a red locus in the i − Ks vs. Ks colour−magnitude diagram, which is broadly consistent with the red sequence of RDCS J0910+5422 determined by Tanaka et al (2008), as shown in Fig. 18b.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…15. At the same time, the fiducial members of XMMU J0338.7+0030 that are classified as elliptical galaxies populate a red locus in the i − Ks vs. Ks colour−magnitude diagram, which is broadly consistent with the red sequence of RDCS J0910+5422 determined by Tanaka et al (2008), as shown in Fig. 18b.…”
Section: Discussionsupporting
confidence: 78%
“…halo assembly (e.g., Tanaka et al 2008; see also Braglia et al 2009, for the most massive clusters at z ∼ 0.3). This could be the case of XMMU J0338.7+0030, according to the projected distribution of its candidate member galaxies (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…One should also consider that for galaxies residing in more extreme density regimes, as those represented by rich cluster cores and not observed in our sample, there could be a residual difference even at redshift ∼1 from the general galaxy population (see, e.g., Tanaka et al 2008). As already suggested in the introduction, however, the physical mechanisms responsible for these differences are presumably not the same as those at play in the group environment.…”
Section: Detection Of the Possible Signature Of Environmental Effectsmentioning
confidence: 69%
“…Current studies aim at establishing whether their abundance evolves with lookback time, with proponents divide into opposite camps (e.g. Andreon 2008;Lidman et al 2008;Crawford et al 2009;Tanaka et al 2008;vs. Gilbank & Balogh 2008;Stott et al 2007).…”
Section: Introductionmentioning
confidence: 99%